Protocol on medico-legal documentation of solitary confinement - Brasholt, Marie; Sveaass, Nora; Pérez Sales, Pau; Marboeuf, Hugo; Cakal, Ergün; Søndergaard, Elna (Torture Journal, 2023)
Introduction. This Protocol originates from a joint project regarding documentation of psychological torture initiated by the Public Committee against Torture in Israel (PCATI), REDRESS and DIGNITY - Danish Institute Against Torture (DIGNITY) in 2015 after the Copenhagen Conference on Psychological Torture. The project is a vehicle to establish a common understanding between health and legal professions as to how to best ensure the most accurate documentation of torture. The aim of the Protocol is to improve documentation of solitary confinement and therefore to clarify the facts of the case so that stronger legal claims can subsequently be submitted to local and international complaints mechanisms. The Protocol has been developed based on a methodology involving a compilation and review of legal and health knowledge on solitary confinement and discussions among the authors and in a group of international experts. Methods and Results. This Protocol is cognisant of the significance of the specific social, cultural and political contexts in which solitary confinement is used. We hope that this Protocol will assist in the discussions between the various stakeholders and provide guidance on what can be documented and how to document torture.